The The Effect of Principal’s Agile Leadership on Generation-Y Teacher’s Performance with Wellbeing as Mediator in SMPK XYZ Under Vuca Context - Ervan Sidharta; Rijanto Purbojo (STKIP Yapis Dompu, 2023)
In the 21st century where technology rapidly develop, COVID-19 attacked education result in rapid changes together with anxiety due to uncertainty. This VUCA affects the wellbeing and performance of workers like generation Y teachers in SMPK XYZ. School principal needs agile leadership for guiding generation Y teachers in their wellbeing and performance in facing VUCA. Mixed method approach is used in this survey study to identify the impact of SMPK XYZ principal’s agile leadership towards generation Y teachers’ performance with wellbeing as mediation. Data gathering was done with questionnaire towards 19 generation Y teachers under the leadership of SMPK XYZ principal and interview with 6 chosen interviewees afterwards. Data is processed through validity and reliability analysis, descriptive statistics, path analysis, and interview thematic analysis. This study shows 11.91% direct and 19.17% indirect positive effect from SMPK XYZ principal’s agile leadership towards generation Y teachers’ performance with wellbeing as mediation. This study also shows positive direct effect of SMPK XYZ principal’s agile leadership towards generation Y teachers’ wellbeing by 22.75%, and the wellbeing towards generation Y teachers’ performance by 84.29%. Thematic analysis supports this statistic analysis and adds that the indirect positive effects from SMPK XYZ principal’s agile leadership towards generation Y teachers’ performance go through all wellbeing dimension, except spiritual wellbeing.